Creative destruction? : economic crises and democracy in Latin America - González González, Francisco Enrique, 1970- (Johns Hopkins University Press, 2012)
Throughout the twentieth century, financial shocks toppled democratic and authoritarian regimes across Latin America. But things began to change in the 1980s. This volume explains why this was the case in Argentina, Chile, and Uruguay.